Markups in a two-country monopolistic competition model of trade with heterogeneous consumers - Aleksandr Oésarin; Valerij Verbus; Irina Bakunina; Vera Silaeva; Marina Silaeva (Journal of Economic Structures, 2020)
The paper develops a two-country monopolistic competition model of trade featuring country-specific consumer tastes. The accounting for heterogeneity in tastes is achieved by assuming different elasticities of substitution in the CES utility function for different country consumers. The proposed framework extends the canonical Krugman's approach by revealing new effects regarding markups response to consumer heterogeneity and trade liberalization. Specifically, the model predicts that, depending on the preference structure, trade liberalization may lead either to decrease or increase in the level of markups, charged by monopolistically competitive firms across destination countries.
Keywords: F12; D43; L13; 330; Heterogeneous consumers; Monopolistic competition; CES utility function; International trade; Markups